2014
DOI: 10.1002/smll.201401343
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Shifting 3D Protein Microstructures with Programmable Directionality via Quantitative Nanoscale Stiffness Modulation

Abstract: The ability to shape-shift in response to a stimulus increases an organism's survivability in nature. Similarly, man-made dynamic and responsive "smart" microtechnology is crucial for the advancement of human technology. Here, 10-30 μm shape-changing 3D BSA protein hydrogel microstructures are fabricated with dynamic, quantitative, directional, and angle-resolved bending via two-photon photolithography. The controlled directional responsiveness is achieved by spatially controlling the cross-linking density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 46 publications
1
80
0
Order By: Relevance
“…It allows to become a standard to introduce and discuss variation of the major factors including laser properties, irradiation conditions, solvent, photoactivator and protein concentration, that can affect the outcome of the process. BSA is also often used due to its unique properties, one of which is pH actuation capability 39,40,62 , as discussed later. Kaehr et al have also shown its potential to be mixed with other …”
Section: Retention Of Protein Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows to become a standard to introduce and discuss variation of the major factors including laser properties, irradiation conditions, solvent, photoactivator and protein concentration, that can affect the outcome of the process. BSA is also often used due to its unique properties, one of which is pH actuation capability 39,40,62 , as discussed later. Kaehr et al have also shown its potential to be mixed with other …”
Section: Retention Of Protein Functionmentioning
confidence: 99%
“…These functions include not only the diverse intrinsic properties of native proteins such as charge transfer, molecule modification and cell-cell communication, but also engineered functions of synthetic proteins. Consequently, the resulting protein structures have been applied to fabricate functional microdevices, including pH-sensitive actuators 39,40 and optical microcomponents 41,42 . The integration of proteinaceous microstructures into commercial polymers 43 and protein-polymer hybrids 44 has also been found to increase mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Protein molecules in aqueous solution can be cross-linked to construct 3D proteinaceous microstructures by the exposure of a focused femtosecond laser along its trajectory in well-resolved and controlled manners [7][8][9]. Such microstructures made of protein have been applied for cell culture scaffolds [10,11], pH-actuators [9,12,13] and optical elements [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Such microstructures made of protein have been applied for cell culture scaffolds [10,11], pH-actuators [9,12,13] and optical elements [13,14]. 3D microstructures made of collagen have been shown to promote cell adhesion [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation